HUBUNGAN EFIKASI DIRI DAN SPIRITUALITAS DENGAN KOPING LANSIA HIPERTENSI DI WILAYAH KELURAHAN GROGOL - Galuh Nurulita Fitriani (2023)
Hypertension is one of the Non-Communicable Diseases (NCDs) which is the most critical health problem in the elderly in Indonesia. Good coping is needed by the elderly with hypertension to support health behaviour. This study aims to determine the relationship between self-efficacy and spirituality with the coping of elderly hypertension in the Grogol Village area. The method used in this study is observational analytic with a cross sectional approach. The sampling technique used quota sampling with a sample size of 150 people. Data collection was carried out using the GSES (General Self-Efficacy Scale), DSES (Daily Spiritual Experience Scale), and brief-cope questionnaires. Based on the results of the analysis through the chi-square test, it was found that there was a relationship between the variables of self-efficacy and coping (P-value = 0.000) and between spirituality and coping (P-value = 0.000) in hypertensive elderly in the Grogol Village area. Self-efficacy and spirituality play an important role in improving coping in elderly people with hypertension so that they are able to adapt and implement appropriate health behaviours. Nursing intervention methods such as education and counseling can be developed for elderly people with hypertension to improve coping and create adaptive behaviour. Future researchers are expected to increase the research domain by expanding other variables such as family support, social support, or material assets.